Proposal and validation of an instrument to measure climate behavior in universities - Rodríguez Jasso, Alan Francisco; Rodríguez Jasso, Lucero de Jesús; Sánchez Limón, Mónica Lorena; Delgado Rivas, Jesús Gerardo (Acta Universitaria, 2023)
The importance of climate change has been strengthened in the last decades, prevailing the need for a change of behavior. The main objective of this research is to establish a validation scale to evaluate the climate behavior of students in Mexican universities based on public climate awareness, social and individual norms, and climate attitude. The method used was a quantitative and confirmatory analysis on the proposed instrument using SmartPLS; the instrument was administered to 166 university students. The results suggest a valid and reliable scale for the evaluation of climate behavior through the proposed variables, empirically supporting the theoretical proposal in the university context and concluding in a support for the established hypothesis. The originality of this study lies on the level of analysis (second order), the model generated, and the subject of study.